Down at the end of lonely street the life and death of Elvis Presley - Brown, Peter H. 1939-; Broeske, Pat H. (Dutton, 1997)
Reveals secrets about Elvis' marriage to Priscilla Beaulieu, his ties to Colonel Tom Parker, the source of his drug addiction, and his death and its aftermath.
Keywords: Presley, Elvis <1935-1977>; Presley, Elvis -- 1935-1977; Rock musicians -- United States -- Biography; USA; Biografie